Synthetic Peptides as Protein Mimics - Groß, Andrea; Hashimoto, Chie; Sticht, Heinrich; Eichler, Jutta (Frontiers in Bioengineering and Biotechnology, 2016)
The design and generation of molecules capable of mimicking the binding and/or functional sites of proteins, represents a promising strategy for the exploration and modulation of protein function through controlled interference with the underlying molecular interactions. Synthetic peptides have proven an excellent type of molecule for the mimicry of protein sites, since such peptides can be generated as exact copies of protein fragments, as well as in diverse chemical modifications, which includes the incorporation of a large range of non-proteinogenic amino acids, as well as the modification of the peptide backbone. Apart from extending the chemical and structural diversity presented by peptides, such modifications also increase the proteolytic stability of the molecules, enhancing their utility for biological applications. This article reviews recent advances by this and other laboratories in the use of synthetic protein mimics to modulate protein function, as well as to provide building blocks for synthetic biology.